2007
DOI: 10.1039/b616678d
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected thermal characteristics of aqueous solutions of poly(2-isopropyl-2-oxazoline)

Abstract: Annealing of dilute aqueous solutions of poly(2-isopropyl-2oxazoline) at above the cloud point leads to the irreversible formation of coagulate particles with hierarchical ordering on two length-scales: micron-sized assemblies of fibrils that measure tens of nanometres across.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 12 publications
6
95
0
1
Order By: Relevance
“…Furthermore, it is observed that these polymer show similar behavior as the poly(2-alkyl-2-oxazoline)s in the second group comprising side-chains with intermediate hydrophobicity. As such, it can be concluded that a favorable hydration shell is also formed with these aromatic poly(2-oxazoline)s as was previously already reported for PhOx [33].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, it is observed that these polymer show similar behavior as the poly(2-alkyl-2-oxazoline)s in the second group comprising side-chains with intermediate hydrophobicity. As such, it can be concluded that a favorable hydration shell is also formed with these aromatic poly(2-oxazoline)s as was previously already reported for PhOx [33].…”
Section: Resultssupporting
confidence: 80%
“…However, little is known about the solution behavior of polymers in water-ethanol mixtures, despite such mixtures being known to exhibit interesting abnormal mixing properties due to the presence of hydration shells around the ethanol molecules [40][41][42]. This peculiar mixing behavior has been demonstrated to result in solubility maxima for several drug molecules in aqueous ethanol [43,44] as well as for poly(methyl methacrylate) [45,46] and several poly(2-oxazoline)s as already mentioned previously [33][34][35].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…O N n Poly(L-proline) PPro [346,347] Precipitated polymer is in the ordered crystalline state; theoretically predicted T Θ = 100 • C for M n = 53,000 g/mol using temperature dependence of the second virial coefficient [346] Helical structure of oligoprolines [348,349] [353] Synthesized using RAFT polymerization [352,353] (continued) 58 V. Aseyev et al Poly(2-substituted-2-oxazoline)s are polymeric non-ionic tertiary polyamides obtained from 2-substituted oxazolines via living cationic ring-opening polymerization [64,[360][361][362][363][364][365]; Poly(2-methyl-2-oxazoline), PMOz, is soluble in water at 0 • C < T < 100 • C; polyoxazolines with ethyl, propyl and isopropyl pendants show the LCST behaviour; the transition is sharp with fast responsivity in comparison to PiPAAm; transition is reversible, and shows no noticeable hysteresis; no polyoxazolines with four or more carbon atoms have been reported to be soluble in water [362,[366][367][368][369][370]; poly(2-alkyl-2-oxazoline)s with 1-7 pendants are crystallizable and form oriented crystalline filaments [365,[371][372][373][374][375][376]; while those with 6-11 reveal glass transition temperatures [365] 27 n N O Poly(2-ethyl-2-oxazoline) PEOz [366,367,370,[377][378][379][380][381][38...…”
mentioning
confidence: 99%
“…PiPropOx undergoes irreversible crystallization upon long-term annealing above 60 °C, resulting in the formation of coagulate particles. 79 Surface modification of such microparticles was enabled via copolymerization of PiPropOx and ButenOx and subsequent thiol-ene reaction with thiol-functionalized sugars. A thermal stability study of thiol-ene glycosylated PButenOx showed that C-S bond cleavage already occurs around 275 °C, while its unmodified analogue was stable up to ~ 405 °C.…”
Section: Applications Of Poly(2-oxazoline)s With Clickable Side Chainsmentioning
confidence: 99%